1992
DOI: 10.1152/ajplung.1992.263.2.l219
|View full text |Cite
|
Sign up to set email alerts
|

Time course of thrombin-induced increase in endothelial permeability: relationship to Ca2+i and inositol polyphosphates

Abstract: The temporal relationship between the alpha-thrombin-induced increase in transendothelial permeability and the alpha-thrombin-mediated changes in several key transmembrane signaling events was examined in confluent monolayers of bovine pulmonary artery endothelial cells (BPAEC). The time courses of inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] generation, changes in cytosolic [Ca2+] ([Ca2+]i), and reorganization of cytoskeletal F-actin were determined to assess the relationship between these events and the onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…The initial peak rise in thrombin-induced in [Ca 2ϩ ] i is attributed to release from intracellular Ca 2ϩ stores as the result of activation of G␣ q (30). Knockdown of PAR3 in endothelial cells using siRNA had no effect on the peak Ca 2ϩ rise.…”
Section: Discussionmentioning
confidence: 98%
“…The initial peak rise in thrombin-induced in [Ca 2ϩ ] i is attributed to release from intracellular Ca 2ϩ stores as the result of activation of G␣ q (30). Knockdown of PAR3 in endothelial cells using siRNA had no effect on the peak Ca 2ϩ rise.…”
Section: Discussionmentioning
confidence: 98%
“…This process is reversible, and focal adhesion kinase plays a role in the reversal of the increased vascular permeability [64] . Thrombin-induced increase in vascular endothelial permeability contributes to the edema seen in inflammatory disorders such as acute lung injury [65,66] . Both the receptor and its downstream signaling pathways are targets for therapeutic intervention [67,68] .…”
Section: Gpcrs and Regulation Of Vascular Endothelial Permeabilitymentioning
confidence: 99%
“…We have also shown that activation of endothelial cell surface protease-activated receptor-1 (PAR-1) by thrombin caused a rapid and transient increase in cytosolic Ca 2ϩ concentration ([Ca 2ϩ ] i ) because of the release of stored Ca 2ϩ and a subsequent Ca 2ϩ entry triggered by store depletion (7,20,30). In endothelial cells, the plasma membrane cation channels known as store-operated cation channels (SOCs) mediate the entry of Ca 2ϩ into the cell (2,27,32).…”
Section: ϩmentioning
confidence: 99%